FLATBED SCANNERS IN GOLOSIIV PLATE ARCHIVE DIGITIZATION - Andruk, V.; Pakuliak, L. (Одеські астрономічні публікації, 2013)
The problems associated with the application of budget flatbed scanners to digitize astronegatives are discussed.